The influence of job stress, workload, and burnout on job satisfaction among paramedics in the emergency department of southern cluster hospital in Johor - Ahmad Izzati, Amir Shariffudin (2024)
Job satisfaction is something that needs to be taken seriously in the field of work, as it can impact an employee's overall performance. Job stress, workload, and burnout have been mentioned in previous literature as negative triggering factors that can influence job satisfaction. The purpose of this descriptive quantitative cross-sectional study was to determine the relationship between job stress, workload, burnout, and job satisfaction among paramedics in the Emergency Department (ED) of Southern Cluster Hospital in Johor. There are four instruments used in this study for data collection. The Minnesota Satisfaction Questionnaire (MSQ) Short Form Scale was used to determine job satisfaction data. The Perceive Stress Scale-10 (PSS-10) was applied to measure job stress level data. The NASA Task Load Index (NASA-TLX) was used to obtain data about workload, and the Copenhagen Burnout Inventory (CBI) was used to measure burnout data. The research data was obtained from the questionnaires that were distributed and answered by 108 respondents to the study. The data was analysed using the Pearson correlation test. The analysis result showed that job stress, workload, and burnout had a strong negative correlation and were significant with job satisfaction. While the regression test showed job stress contributes the most to job satisfaction, Further studies on the variables that may influence job satisfaction among paramedics in the ED are recommended to determine the problems and interventions to be taken. Proactive measures such as promoting work-life balance and offering comprehensive support programmes by the management team may increase job satisfaction among paramedics in the ED.